Cerebral salt wasting syndrome - Dholke, Harshal; Campos, Ann; Reddy, C. Naresh K.; Panigrahi, Manas K. (Journal of Neuroanaesthesiology and Critical Care, 2016)
Traumatic brain injury (TBI) is on the rise, especially in today’s fast-paced world. TBI requires not only neurosurgical expertise but also neurointensivist involvement for a better outcome. Disturbances of sodium balance are common in patients with brain injury, as the central nervous system plays a major role in sodium regulation. Hyponatraemia, defined as serum sodium <135 meq/L is commonly seen and is especially deleterious as it can contribute to cerebral oedema in these patients. Syndrome of inappropriate antidiuretic hormone secretion (SIADH), is the most well-known cause of hyponatraemia in this subset of patients. Cerebral Salt Wasting Syndrome (CSWS), leading to renal sodium loss is an important cause of hyponatraemia in patients with TBI. Although incompletely studied, decreased renal sympathetic responses and cerebral natriuretic factors play a role in the pathogenesis of CSWS. Maintaining a positive sodium balance and adequate hydration can help in the treatment. It is important to differentiate between SIADH and CSWS when trying to ascertain a case for patients with acute brain injury, as the treatment of the two are diametrically opposite.
Keywords: Brain natriuretic peptide; cerebral salt wasting; conivaptan; fludrocortisone; hypertonic saline; hyponatraemia